2015
DOI: 10.1080/21645515.2015.1017694
|View full text |Cite
|
Sign up to set email alerts
|

Best vaccination practice and medically attended injection site events following deltoid intramuscular injection

Abstract: Analysis of medically attended injection site events data provides a vehicle to appreciate the inadequacies of vaccination practice for deltoid intramuscular injection and to develop best practice procedures. These data can be divided into 3 groups; nerve palsies, musculoskeletal injuries and cutaneous reactions and reflect inappropriate site of injection, needle over or under penetration, local sepsis and vascular complications. The aim of this review is to formulate best vaccination practice procedures for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 83 publications
0
74
0
5
Order By: Relevance
“…Besides, literature shows that nurses have not received any kind of training other than basic training of IM injection method, although IM medication administration causes iatrogenic complications. 6,27 Study by Hensel and Springmyer revealed that nurses are not informed about current recommendations issued by professional nursing institutions and they continue their profession with practices taught during their basic training. 28 The nurses witness traditional ritualized injection administration applied by other nurses in many practices and thereby, they do not revise current research about the issue most of the time.…”
Section: Nurses' Features Of Im Injection Administrationmentioning
confidence: 99%
“…Besides, literature shows that nurses have not received any kind of training other than basic training of IM injection method, although IM medication administration causes iatrogenic complications. 6,27 Study by Hensel and Springmyer revealed that nurses are not informed about current recommendations issued by professional nursing institutions and they continue their profession with practices taught during their basic training. 28 The nurses witness traditional ritualized injection administration applied by other nurses in many practices and thereby, they do not revise current research about the issue most of the time.…”
Section: Nurses' Features Of Im Injection Administrationmentioning
confidence: 99%
“…[2,11,[44][45][46] Critical assessments of patient weight, BMI, gender and injection site, needle length, volume of medication before administering IM injections is important and therefore should drive practice change.…”
Section: Injection Depthmentioning
confidence: 99%
“…However, upper arm and shoulder injury related to vaccine administration is an emerging, and likely under-reported, phenomenon. [12,[15][16][17] The standard deltoid landmark needs to be updated: three fingers below the acromion should be considered the upper (superior) boundary for safe deltoid injections, and an additional lower boundary, at the axillary line, should be added for optimal client safety. The safe injection zone is between these upper and lower boundaries, along the coronal (vertical) axis of the outer aspect of the client's arm.…”
Section: Discussionmentioning
confidence: 99%